A Study on the Impact of Emotional Intelligence on Employee Performance with Special Reference to IT/ITES sector in Chennai City - Parveen.S.M, Majeetha; Mohan, Nirmala (International Journal of Psychosocial Rehabilitation, 2020)
Emotional intelligence refers to the capability of a person to manage and control his or her emotions and possess the ability to control the emotions of others as well. In other words, they can influence the emotions of other people also. Emotional intelligence is a very important skill in leadership. It is said to have five main elements such as self-awareness, self-regulation, motivation, empathy, and social skills.Emotional intelligence is the ability to identify and manage own emotions and the emotions of others. It is generally said to include the ability to identify own emotions and those of others, to harness emotions and apply them to tasks like thinking and problems solving, to manage emotions, including the ability to regulate own emotions, and the ability to cheer up or calm down another person.